Pelestarian Keroncong Dengan Pembelajaran Berbasis Masyarakat oleh O.K Tiga Negeri di Kabupaten Rembang - Daggo Alanta Dewa Daggo; Abdul Rachman (Program Studi Pendidikan Musik FBS UNP, 2024)
Purpose: This study aims to identify the activities and community-based learning processes within the Tiga Negeri Keroncong Orchestra in Gedongmulyo Village, Lasem District, Rembang Regency. Method: The research method used is descriptive qualitative. Data collection was carried out through observation, interviews, and documentation. Results and Discussion: The study's findings indicate that efforts to preserve keroncong music by the Tiga Negeri Keroncong Orchestra are implemented through several activities, including weekly routine practice, performances both within and outside the city, and composing songs. The preservation of keroncong music is also conducted through community-based learning aimed at introducing keroncong music to a wider audience. This learning process involves six essential components: learning objectives, learners, teachers, learning materials, facilities and infrastructure, and the learning process. Conclusion: This study highlights the importance of collaboration between cultural actors and the community in safeguarding local cultural heritage through creative and systematic activities, providing new insights into community-based cultural preservation.